Clinical significance of late diastolic tissue doppler parameters after onset of STEMI: from the view point of the timing of the echocardipography. (25th November 2020) - Iwahashi, N; Kirigaya, J; Horii, M; Abe, T; Akiyama, E; Okada, K; Matsuzawa, Y; Maejima, N; Hibi, K; Kosuge, M; Ebina, T; Tamura, K; et al.
Abstract: Background: The early transmitral flow velocity (E) divided by the early diastolic velocity of the mitral valve annulus (e') is referred to as the "E/e' ratio, " is useful even for ST elevation acute myocardial infarction (STEMI). However, the role of late diastolic velocity (a') which reveals the atrial function for STEMI is still unclear. Objectives: We evaluated the clinical usefulness of tissue Doppler including atrial function for a first-time STEMI by long time follow up. Furthermore, we evaluated the meaning of each parameters by performing immediately after PCI or 2 weeks later. Methods: We treated consecutive 571 first-time STEMI patients by immediate PCI within 12 hours after onset, and we examined 270 patients at immediately after PCI (GroupA, 65 years, 250 male) and 301 patients at 2 weeks after onset (GroupB, 64 years, 243 male). We examined trans mitral flow and TDI, then defined E/e' as LV filling pressure and A/a' as left atrial function. We followed them for a long time (>5 years). The primary end point (PE) was cardiac death or re-admission for heart failure (HF). Results: We followed the patients in Group A for 10 years, Group B for 5 years. PE occurred in 64 patients in GroupA during 10 years, and 45 patients in GroupB during 5 years. We analyzed the univariate and multivariate Cox hazard analyses and we compared e' and a', E/e' and A/a' (Table). In GroupA, a' and A/a' were the independent predictors, on the other hand neither a' nor A/a' were the predictors in GroupB. E/e' was an independent predictor both in GroupA and B. Conclusion: TDI parameters have different meanings by the timing of echocardiography after onset of a first-time STEMI. These results demonstrated that atrial dysfunction immediately after onset of STEMI suggests the poor prognosis after STEMI. Funding Acknowledgement: Type of funding source: None